Work-related stressors among hospital physicians: a qualitative interview study in the Tokyo metropolitan area - Daisuke Son; Yuko Ihara; Masahiro Nochi; Ryu Takizawa (BMJ Open)
Objectives We explored Japanese physicians’ work-related stressors and identified those unique to this population, as well as clarified the influence of cultural and medical system diversity on these stressors to determine the content of future stress-reducing interventions for hospital physicians in Japan.Design We conducted a semistructured, face-to-face interview-based qualitative study between August and October 2017. The collected data were analysed using the grounded theory approach.Setting Hospitals around the Tokyo metropolitan area, Japan.Participants Sixteen hospital physicians (mean age (SD)=33.9 (4.2) years; 11 men, 5 women). Seven worked in internal medicine and nine in surgery.Results We found unique stressors related to the Japanese medical system and culture, such as continuous all-day work after night shifts, and a hierarchical organisational system called Ikyoku. The results also indicated that Japanese physicians shared several stressors with Western physicians, such as sleep deprivation, high pressure and the limits of medicine.Conclusions Our study clarifies some sources of work-related stressors among hospital physicians in Japan. While the key components of Western interventions might be useful in a Japanese context, the original evidence obtained from this study highlights the necessity of initiating interventions addressing the unique stressors of Japanese physicians. To reduce physicians’ stress and enhance their well-being, psychological interventions for hospital physicians must be introduced in Japan.